Familial aggregation of albuminuria and arterial hypertension in an Aboriginal Australian community and the contribution of variants in ACE and TP53. Issue 1 (December 2016) - Duffy, David; McDonald, Stephen; Hayhurst, Beverley; Panagiotopoulos, Sianna; Smith, Trudy; Wang, Xing; Wilcken, David; Duarte, Natalia; Mathews, John; Hoy, Wendy
Abstract Background Aboriginal Australians are at high risk of cardiovascular, metabolic and renal diseases, resulting in a marked reduction in life expectancy when compared to the rest of the Australian population. This is partly due to recognized environmental and lifestyle risk factors, but a contribution of genetic susceptibility is also likely. Methods Using results from a comprehensive survey of one community (N = 1350 examined individuals), we have tested for familial aggregation of plasma glucose, arterial blood pressure, albuminuria (measured as urinary albumin to creatinine ratio, UACR) and estimated glomerular filtration rate (eGFR), and quantified the contribution of variation at four candidate genes (ACE;TP53 ;ENOS3 ;MTHFR ). Results In the subsample of 357 individuals with complete genotype and phenotype data we showed that both UACR (h2 = 64%) and blood pressure (sBP h2 = 29%, dBP, h2 = 11%) were significantly heritable. TheACE insertion-deletion (P = 0.0009) andTP53 codon72 polymorphisms (P = 0.003) together contributed approximately 15% of the total heritability of UACR, with an effect of ACE genotype on BP also clearly evident. Conclusions While the effects of theACE insertion-deletion on risk of renal disease (especially in the setting of diabetes) are well recognized, this is only the second study to implicate p53 genotype as a risk factor for albuminuria - the other being an earlier study we performed in a different Aboriginal community (McDonald et al., J Am Soc Nephrol 13: 677-83, 2002). We conclude that there are significant genetic contributions to the high prevalence of chronic diseases observed in this population.